EFFECTIVENESS OF BLENDED LEARNING WITH THE FLIPPED CLASSROOM MODEL ON SHOCHUUKYUU BUNPOU IN 21TH-CENTURY DYNAMICS SKILL TOWARDS JAPANESE LANGUAGE EDUCATION STUDY PROGRAM MUHAMMADIYAH UNIVERSITY PROF. DR. HAMKA - Agustina Karnawati, Rita (IJLECR (International Journal of Language Education and Cultural Review), 2020)
Learning using Blendedlearning with the Flippedclassroom model. This study aims to analyze the effectiveness of Blendedlearning with the Flippedclassroom model in Shochuukyuubunpou courses in the second semester students of Japanese Language Education, Muhammadiyah University, Prof Dr Hamka2019-2020.The model used in research this is a quasi experiment with a pretest posttest one group design. The sample consisted of 20 respondents in class 2. The test result between the lecture modeland the Flipp The Teacher model sig (2 tailed)that is 0.000smaller than the 0.05 significance level. Then it can be concluded that the are significant differences between students learning outcomes using the lecture model and The Flip The Teacher model. From the Normalized Gain test result, the Normalized Gain score for the Flip The Teacher model is 0.369 so that this model has moderate effectiveness. It can be concluded that the percentage effectiveness of the lecture model is smaller than the Flip the Teacher in Shochuukyuubunpou courses in the second semester of UHAMKA Japanese Language Education in 2019-2020 Keyword : Shochuukyuubunpou,Bended Learning, Flip the Teacher